A novel soft cardiac assist device based on a dielectric elastomer augmented aorta: An in vivo study. Issue 2 (22nd August 2022) - Martinez, Thomas; Jahren, Silje Ekroll; Walter, Armando; Chavanne, Jonathan; Clavica, Francesco; Ferrari, Lorenzo; Heinisch, Paul Philipp; Casoni, Daniela; Haeberlin, Andreas; Luedi, Markus M.; Obrist, Dominik; Carrel, Thierry; et al.
Abstract: Although heart transplant is the preferred solution for patients suffering from heart failures, cardiac assist devices remain key substitute therapies. Among them, aortic augmentation using dielectric elastomer actuators (DEAs) might be an alternative technological application for the future. The electrically driven actuator does not require bulky pneumatic elements (such as conventional intra‐aortic balloon pumps) and conforms tightly to the aorta thanks to the manufacturing method presented here. In this study, the proposed DEA‐based device replaces a section of the aorta and acts as a counterpulsation device. The feasibility and validation of in vivo implantation of the device into the descending aorta in a porcine model, and the level of support provided to the heart are investigated. Additionally, the influence of the activation profile and delay compared to the start of systole is studied. We demonstrate that an activation of the DEA just before the start of systole (30 ms at 100 bpm) and deactivation just after the start of diastole (0–30 ms) leads to an optimal assistance of the heart with a maximum energy provided by the DEA. The end‐diastolic and left ventricular pressures were lowered by up to 5% and 1%, respectively, compared to baseline. The early diastolic pressure was augmented in average by up to 2%.